Nitrate contamination and temporal trends in volcanic Barva and Colima aquifers (1988-2018), in an urban and agriculture-dominated region, Costa Rica - Madrigal-Solís, Helga (2019)
In the great metropolitan area (GAM) of Costa Rica, 65% of the population, equivalent to 1.7 million people, is supplied by the most important volcanic aquifers in the country: Barva, phreatic and the most superficial, colima superior, and colima inferior, both phreatic in some sectors and confined in others. The GAM has the highest urban and industrial growth and, in addition, agricultural activities related to the intensive use of nitrogen fertilizers. about 70% of the population use septic tanks for the disposal of domestic wastewater and, in most cases, these systems lack the appropriate technical specifications in their construction. due to the risk of contamination to which the groundwater is exposed, this research aimed to evaluate temporal trends in nitrate concentration in Barva, colima superior, and colima inferior aquifers. in total, 43 sites have been monitored, some from 1988 to 2018 (1,388 observations). samples were analyzed in the Environmental Hydrology Laboratory, Universidad Nacional, Costa Rica, quarterly.